Manajemen Pengelolaan Sampah di Kabupaten Jepara - Alam - Sabdani; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2020)
Garbage is a material of residual living creature that is not used anymore and released to nature in the form of solids, liquids or gases. Trash must be managed properly to avoid the bad effects of garbage. Jepara Regency Government is currently in dealing with garbage problems doing waste management by issuing the rule of Regent No. 46 year 2018 or commonly called Jakstrada waste management. In Jakstrada, there are programs from the garbage management Jakstrada which is run by the Environment Department of Jepara District which is still not yet running according to the plan Jakstrada. This research aims to know the management of waste management of Jakstrada District Jepara. This research approaches qualitative descriptive. Data collected with the technique of wawancar. Qualitative analysis is strengthened with data. This study found that Jakstrada in the waste Management run Environment Office of Jepara District has not walked as planned because there is a problem of processing management. The problem of the undercooked Jakstrada planning and the target is too high. The issue of organizing is the lack of budget and human resources to run Jakstrada programs. In the implementation, some Jakstrada programs did not run because of the poor organizing and the obstacles that were asked during the management of Jakstrada programs. The conclusion that can be withdrawn from this research is the management of waste management that is currently done by the government of Jepara district has not run properly, because in the stages of management there are still shortcomings and mistakes. Because of this that makes the management of waste is not currently running according to Jakstrada plan. In addition, in its management it also experiences sharing barriers. Researchers suggest management of waste management that is currently done by the government of Jepara district has not been running properly, because in the stage of management there are still shortcomings and mistakes. Because of this that makes the management of waste is not currently running according to Jakstrada plan. In addition, in its management it also experiences sharing barriers